2021
DOI: 10.1172/jci.insight.154350
|View full text |Cite
|
Sign up to set email alerts
|

Computational and biophysical determination of pathogenicity of variants of unknown significance in cardiac thin filament

Abstract: Point mutations within sarcomeric proteins have been associated with altered function and cardiomyopathy development. Difficulties remain, however, in establishing the pathogenic potential of individual mutations, often limiting the use of genotype in management of affected families. To directly address this challenge, we utilized our all-atom computational model of the human full cardiac thin filament (CTF) to predict how sequence substitutions in CTF proteins might affect structure and dynamics on an atomist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…However, with increasing use of high-sensitivity genetic testing there is a constantly expanding list of variants of unknown significance, often contributing more to patient confusion and undue distress rather than clinical intervention. As a potential solution, Mason et al have demonstrated the use of a high-fidelity computational model of the cardiac thin filament to predict point mutation behavior at the atomic level, suggesting the future possibility of characterization of a given VUS without necessitating animal models or familial studies ( 158 ). But until mutation characterization matches available screening diagnostics, clinicians should be encouraged to limit any interpretation of genetic testing to only well-understood variants.…”
Section: The Need For Targeted Therapies For Thin Filament Cardiomyop...mentioning
confidence: 99%
“…However, with increasing use of high-sensitivity genetic testing there is a constantly expanding list of variants of unknown significance, often contributing more to patient confusion and undue distress rather than clinical intervention. As a potential solution, Mason et al have demonstrated the use of a high-fidelity computational model of the cardiac thin filament to predict point mutation behavior at the atomic level, suggesting the future possibility of characterization of a given VUS without necessitating animal models or familial studies ( 158 ). But until mutation characterization matches available screening diagnostics, clinicians should be encouraged to limit any interpretation of genetic testing to only well-understood variants.…”
Section: The Need For Targeted Therapies For Thin Filament Cardiomyop...mentioning
confidence: 99%
“…Structures utilized in this study were created starting from the cryo-EM structures published by Yamada, Namba, and Fujii, as previously described, , which provided structures for both Ca 2+ -saturated and -unsaturated conformations of the CTF (PDB 6KN8 and 6KN7, respectively). In the context of saturation of the CTF, a fully saturated system refers to Ca 2+ bound to site II of cTnC, while unsaturated refers to no Ca 2+ bound to site II of cTnC.…”
Section: Methodsmentioning
confidence: 99%
“…All structured fragments were aligned and the proteins were subjected to minimization until all bonds and angles were acceptable values. Any clashing of proteins was resolved by rotating dihedral angles in the unstructured regions, as previously described. , The helical pitch of Tm in the Yamada structure was corrected to agree with the protein docking study by Pavadai et al, allowing Tm to span 7 actin monomers instead of the 6 monomers in the original pdb. The structure for the cTnI C-terminal domain of the Ca 2+ -unsaturated state was also corrected to agree with the docking study by Lehman et al, which found a more energetically favorable location compared to the originally published structure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations